Recycling and disposal of lithium batteries: an economical and environmental approach - Rahman, Mohammed Ataur; Afroz, Rafia; Safrin, Mohd (IIUM Press, 2017)
The adoption of lithium-ion battery technology for electric vehicles/hybrid electric vehicles (EV/HEV) has recently received attention worldwide. The price of cobalt (Co) and lithium (Li) has increased due to the production of EV/HEV. A used lithium battery is a valuable source of active metals (Co, Li, and Al) and the optimal way of extracting these metals from this waste is still studied. The focus of this paper is to recover active metals using the hydrometallurgical method on a laboratory scale with a 48.8 Wh battery to reveal economic and environmental benefits. Calcination of extracted active metals as pre-thermal treatment has been conducted at 700°C to remove the organic compounds from the surface of active metals. The experiment has been conducted and the result shows that the recovery of active metals (cathode) is 41% of the cell cathode and 8.5% of the cell anode materials, which represent 48.8% and 23.4% of the cathode and anode cell material price, respectively. By recycling about 47.34% of the battery active metals, emissions can be reduced by 47.61% for battery metal production and 60.7% for disposal transportation of the used battery. The total emission can be reduced by about 52.85% by recycling the active metals in used batteries.